Higher Body Mass Index Correlates with Increased Tumor Aggressiveness in Prostate Adenocarcinoma: Evidence From a Hospital-Based Cross-Sectional Study - Adam Yulianto; Hasroni Fathurrahman (UMSU, 2026)
Prostate cancer remains a major cause of cancer-related mortality in men and represents the most common urological malignancy. Age and obesity have long been recognized as important risk factors that may shape both tumor differentiation and progression. The Gleason scoring system, used to grade prostate adenocarcinoma, captures how differentiated the tumor cells are and helps estimate its level of aggressiveness. This study aimed to evaluate the association between age and BMI with the histopathological grade of prostate adenocarcinoma at Dr. Pirngadi General Hospital Medan. A cross-sectional analytical study was conducted using secondary data from medical records of 70 patients diagnosed with prostate adenocarcinoma. Statistical analysis was performed using Spearman’s correlation test. The results showed that 6 patients (8.6%) were aged 60 years, 41 patients (58.6%) had BMI ≥23 kg/m², and 28 patients (40%) presented with Gleason scores of 8–10. There was no statistically significant association between age and histopathological grade (p = 0.571). A statistically significant but weak positive correlation was identified between BMI and histopathological grade (p = 0.003, r = 0.347). These findings indicate that BMI may influence the degree of tumor differentiation and should be considered in the pathological and clinical evaluation of prostate cancer.